Hegemoni Filsafat Yunani dalam Pemikiran Pendidikan Islam - Idris, Muh. (Fakultas Tarbiyah dan Ilmu Keguruan, Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2012)
Having contact with Greece philosophy thought, Moslems are inspired and obsessed to develop knowledge. In the historical spectrum of thought development, Moslems have shown the significant progress in the era of Ummayah and it came to the highest level in the era of Abbasiyah. In that historical context, it can be seen from many experts of Moslem in various field of knowledge such as Al-Kindi (801-837), Al-Farabi (W.950), and Ibn Maskawaih (W.1030) who concern in the field of philosophy; Ibn Sina (980-1037) and Ibn Bajah (1160-1138) who are experts in medicine, Jabir Ibn Hayyan (720-815) and Al-Khawarizmi (780-850) who are experts in chemistry and mathematic, and also Al-Thabari (839-922), an expert in history and law. In the historical perspective, it is clear that the body construction of Islamic knowledge which is broad and deep was established on the basis of cooperation and openness with other nations including Greece.